The impact of the Russian-Ukrainian war on the energy sector in the EU - Brenzovych, Anna; Zeynalov, Ayaz; Antal, Jarolím, 1986-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The master's thesis examines the impact of the Russia-Ukraine war on the European Union's energy sector, with a focus on natural gas supply, pricing and the wider implications for EU energy policy. It assesses the extent to which the EU is dependent on Russian energy and how the conflict has prompted a strategic shift in the EU towards diversifying energy sources and increasing the sustainability of energy consumption. Empirical research shows significant changes in the structure of electricity consumption, as well as a marked increase in the use of and investment in renewable energy sources caused by the crisis. The study uses econometric models to analyse changes in energy pricing and consumption, confirming that the crisis and price volatility have a significant impact on energy use and accelerate the transition to renewable energy sources. This thesis contributes to the discourse on energy dependence by offering insights into the effectiveness of the EU's response to energy crises and the ongoing evolution of its energy policy.
Vedoucí práce: Ayaz Zeynalov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses